Study of the value and its epistemological foundation for a culture of peace - Gregorio Villegas Cobián; José Álvarez Rodríguez; Daniel Álvarez Ferrándiz (Revista de Cultura de Paz, 2019)
Through this paper we present a theoretical perspective on the concept of value and proposals for its implementation. We analyze the evolution of values and their particularities through different generations. This will allow us to appreciate the evolution of the concept and its particularities. Focused on values, we aim to link the study of values from perspectives that contribute to reveal and raise awareness of the transversal importance of values in educational projects and reforms that impact the life and development of new generations. The results of this historical analysis confirms the importance and potential provided by a value-oriented education.